Induction of FOXP3 expression in naive human CD4(+)FOXP3(−) T cells by T-cell receptor stimulation is transforming growth factor-β–dependent but does not confer a regulatory phenotype - Tran, Dat Q. (American Society of Hematology, 2007)
Thymic-derived natural T-regulatory cells (nTregs) are important for the induction of self-tolerance and the control of autoimmunity. Murine CD4(+)CD25(−)Foxp3(−) cells can be induced to express Foxp3 after T-cell receptor (TCR) activation in the presence of transforming growth factor β (TGFβ) and are phenotypically similar to nTregs. Some studies have suggested that TCR stimulation of human CD4(+)CD25(−) cells results in the induction of transient expression of FOXP3, but that the induced cells lack a regulatory phenotype. We demonstrate here that TCR stimulation alone was insufficient to induce FOXP3 expression in the absence of TGFβ, whereas high levels of FOXP3 expression could be induced in the presence of TGFβ. Although FOXP3 expression was stable, the TGFβ-induced FOXP3(+) T cells were neither anergic nor suppressive and produced high levels of effector cytokines. These results suggest that even high levels of FOXP3 expression are insufficient to define a human CD4(+) T cell as a T-regulatory cell.